Spatiotemporal Analysis of Dengue Infection Between 2005 and 2010 - Ali, Sarwa; Corner, Robert; Hashizume, M. (Springer Geography, 2013)
The high incidence of dengue fever in Dhaka is a constant threat to the population and a recurring problem for the health authorities. This chapter investigates the spatial and temporal epidemiology of dengue fever between 2005 and 2010. This epidemiological analysis provided important information about the pattern of the virus cases with standard deviation ellipses being used for directional examination of the incidences. To investigate spatial dependencies and examine the occurrence pattern for clustering, Moran’s I and Local Indicators of Spatial Association (LISA) analysis were utilised. Results showed that there was obvious spatial autocorrelation as well as significant clustering of dengue cases in Dhaka, revealing that the virus is concentrated around the heart of the city.